Building Exoskeletons for the Integrated Retrofit of Social Housing - Scuderi, Giuliana (Salehan Institute of Higher Education, 2016)
In Europe, most of the social housing heritage, built before the 1980s, suffers of architectural and functional obsolescence and seismic vulnerability, raising questions about the future of the cities and their inhabitants. In an era of environmental emergency and lack of resources demolition and reconstruction is not a sustainable alternative. A multi-purpose campaign of architectural, functional and structural retrofit is fundamental but the complex information and requirements to handle require integrated and innovative solutions. The bio-mimicry design approach led to the definition of the â€œbuilding exoskeletonâ€: an external steel frame, two or three-dimensional, encapsulating the existing building and provided of shape memory alloys-based devices for passive seismic dissipation. The simplicity of the structure gives high flexibility in the definition of the new architectural features and functional performances, adapting to the changing necessities on both space and time scales. The energy performances result also radically improved. The efficiency of this scheme to improve the seismic response of the constructions is verified for a real case study â€“ a concrete frame with brick infill â€“ through static and dynamic nonlinear analyses with the software SAP2000. Finally, the economic and technical feasibility of the proposal is discussed together with the implications of the project and the possible developments.